Right atrial appendage thrombus with atrial infarct in a case of thyrotoxicosis: An autopsy report - Lanjewar D; Ramraje Sushma; Lanjewar Sonali (Wolters Kluwer Medknow Publications, 2010)
Cardiac function has long been known to be altered in patients with thyrotoxicosis and atrial fibrillation occurs in patients with hyperthyroidism. In addition to its disabling symptoms, atrial fibrillation is a strong risk factor for systemic embolism, especially with regard to cerebral circulation. A right atrial appendage thrombus formation in atrial fibrillation is a rare phenomenon. In this report, we describe a case of a 30-year-old female, who suffered from hyperthyroidism and subsequently developed atrial fibrillation and a right atrial appendage thrombus with infarction of right atrial appendage.